Beyond the Highlight Reel: An Exploratory Study of Negative Life Event Disclosures on Social Networking Sites - Rottenkolber, Maria (My University, 2023)
Users of online social networks are commonly exposed to selective content from their social connections showcasing the positive aspects of their lives, often referred to as highlight reels. Personal posts about the downsides of life are the exception rather than the rule on social networking sites. This explains why scant scholarly attention has been devoted to understanding why users decide to engage in such a behavior against the odds and how this public self-disclosure affects them. Based on qualitative interviews with sixteen users of online social networks, I explored the factors that drive users to publicly disclose a negative life event on an online social network and the outcomes they perceive as a result of their post. Drawing on the Disclosure Process Model (Chaudoir & Fisher, 2010), the empirical findings of this study were integrated into a conceptual model which offers a comprehensive picture of this seemingly counterintuitive behavior: The decision-making process starts with motives becoming salient, ranging from self-focused to other-focused to social contextual-focused motives. The outcome process entails the favorable or unfavorable mediating reactions received in response to the post, which partially explain the outcomes disclosers perceive at the individual, interpersonal, and network level. This thesis is a first contribution towards a holistic understanding of negative life event disclosures on social networking sites and highlights the multifaceted, multifunctional, and prosocial nature of this phenomenon, which has been overlooked in previous literature. Contrary to the prevailing trend in information systems research that paints a comparatively negative picture of social media use, this study contributes to research on the bright sides of social media platforms. Propositions for social network users and platforms that allow to leverage negative life event disclosures for positive purposes constitute valuable practical implications of this research.
Keywords: self-disclosure, disclosure process, social networking sites, online social networks, negative life events, physical health, mental health